Respuesta :
Let's solve your equation step-by-step:
It's always easiest to rewrite the equation, so let's do that -
5 - 1/2x = 12
Step 1) Simplify both sides of the equation
-1/2x + 5 = 12
Step 2) Subtract 5 from both sides
-1/2x = 7
Step 3) Multiply both sides by 2/(-1)
(2/-1) * (-1/2x) = (2/-1) * 7
x = -14
FINAL ANSWER --
x = -14
↑ ↑ ↑ Hope this helps! :D
5- 1/2x= 12
⇒ -1/2x= 12-5
⇒ -1/2x= 7
⇒ x= 7/(-1/2)
⇒ x= 7* (-2/1)
⇒ x= -14
Final answer: x=-14~
⇒ -1/2x= 12-5
⇒ -1/2x= 7
⇒ x= 7/(-1/2)
⇒ x= 7* (-2/1)
⇒ x= -14
Final answer: x=-14~